2015
DOI: 10.1088/1367-2630/17/8/083055
|View full text |Cite
|
Sign up to set email alerts
|

1/fnoise on the brink of wet granular melting

Abstract: The collective behavior of a two-dimensional wet granular cluster under horizontal swirling motions is investigated experimentally. Depending on the balance between the energy injection and dissipation, the cluster evolves into various nonequilibrium stationary states with strong internal structure fluctuations with time. Quantitative characterizations of the fluctuations with the bond orientational order parameter q 6 reveal power spectra of the form a f with the exponent α closely related to the stationary s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Here, we focus on the case of a liquid film covering the solid bodies under impact, in order to shed light on the collective behavior of wet granular matter at a particle level. Recent investigations have revealed that clustering [24,25], phase transitions [26][27][28][29] as well as pattern formation [30,31] of wet granular matter are often related to the 'microscopic' particle-particle interactions, among which the wetting liquid plays an important role. Because the presence of a liquid film as thin as a few nanometers can be sufficient to influence the rigidity of granular matter substantially [32,33], it is essential to consider such an influence in the omnipresent applications.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we focus on the case of a liquid film covering the solid bodies under impact, in order to shed light on the collective behavior of wet granular matter at a particle level. Recent investigations have revealed that clustering [24,25], phase transitions [26][27][28][29] as well as pattern formation [30,31] of wet granular matter are often related to the 'microscopic' particle-particle interactions, among which the wetting liquid plays an important role. Because the presence of a liquid film as thin as a few nanometers can be sufficient to influence the rigidity of granular matter substantially [32,33], it is essential to consider such an influence in the omnipresent applications.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the fact that moisture is ubiquitous in nature and its influence on the collective behavior of granular matter is inevitable 42,43 , there has been a growing interest in partially wet granular matter [44][45][46] . Due to the cohesive interactions induced by liquid bridges formed between adjacent particles, the transitions between different stationary states in wet granular matter exhibit interesting features such as phase separation and surface melting in comparison to its dry counterpart [47][48][49][50][51][52][53][54] . For the same reason, an oscillated wet granular layer has a different pattern forming scenario: Instead of instabilities reminiscent of Faraday crispations 32,34,36 , period tripling induced rotating spirals and propagating kink-wave fronts were found to dominate in a wet granular liquid [55][56][57] .…”
Section: Introductionmentioning
confidence: 99%
“…A class of models of 1/f noise relevant for driven nonequilibrium systems involves the self-organized criticality (SOC) [18][19][20][21]. SOC refers to the tendency of nonequilibrium systems driven by slow constant energy input to organize themselves into a correlated state where all scales are relevant [19].…”
Section: Introductionmentioning
confidence: 99%